2020
DOI: 10.5194/acp-20-13591-2020
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of atmospheric transport and biomass burning on the inter-annual variation in black carbon aerosols over the Tibetan Plateau

Abstract: Abstract. Atmospheric black carbon (BC) in the Tibetan Plateau (TP) can largely impact regional and global climate. Still, studies on the inter-annual variation in atmospheric BC over the TP and associated variation in BC sources and controlling factors are rather limited. In this study, we characterize the variations in atmospheric BC over the TP surface layer through analysis of 20-year (1995–2014) simulations from a global chemical transport model, GEOS-Chem. The results show that surface BC concentrations … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…Figure 8c shows the relative BC contributions from regional sources to WLG. We identified three main BC source regions with respect to WLG, including NCC (56.1%), NWC (17.5%), and INP (12.1%), which is similar to the results of previous studies (Han et al, 2020;Yang et al, 2018;R. Zhang et al, 2015).…”
Section: Modeled Contribution Of Different Regions To Wlg Bcsupporting
confidence: 87%
“…Figure 8c shows the relative BC contributions from regional sources to WLG. We identified three main BC source regions with respect to WLG, including NCC (56.1%), NWC (17.5%), and INP (12.1%), which is similar to the results of previous studies (Han et al, 2020;Yang et al, 2018;R. Zhang et al, 2015).…”
Section: Modeled Contribution Of Different Regions To Wlg Bcsupporting
confidence: 87%
“…On one hand, anthropogenic aerosol from low and middle latitudes can disturb the Arctic atmosphere, especially from Eurasia. On the other hand, stable atmospheric status with less precipitation occurs in the Arctic winter, which makes it difficult for aerosols to be removed by wet deposition (Garrett et al, 2010;Heintzenberg, 1989). As shown in Fig.…”
Section: The Multi-year-averaged Seasonal Variation In Aodmentioning
confidence: 99%
“…Sensitivity simulation also requires expensive computational resources, which results in most global simulations of pollutants running at coarse horizontal resolutions ranging from 1 • × 1 • to 5 • × 5 • , such as 4 • × 5 • in J. , 2 • × 2.5 • in Han et al (2020), 1 • × 1 • in Crippa et al (2019), and 2.8 • × 2.8 • in Nagashima et al (2017), and S-R relationships are limited to a few regions (e.g., Europe, North America, East Asia, South Asia). Many recent studies have revealed that horizontal resolution has a considerable influence on model performance in air quality simulations (Lin et al, 2010;Tao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%